Optimizing Contrast Media Injection Protocols in Computed Tomography Angiography at Different Tube Voltages: Evaluation in a Circulation Phantom. Issue 5 (September 2017) - Caruso, Damiano; Eid, Marwen; Schoepf, U. Joseph; De Santis, Domenico; Varga-Szemes, Akos; Mangold, Stefanie; Canstein, Christian; Lesslie, Virginia W.; Fuller, Stephen R.; Ball, B. Devon; Laghi, Andrea; De Cecco, Carlo N.
Abstract : Objectives: The aim of this study was to investigate the minimum iodine delivery rate (IDR) and contrast media (CM) volume required for diagnostic contrast enhancement of 350 HU (Hounsfield units) in the ascending aorta at different kV settings. Methods: Dynamic computed tomography acquisitions from 70 to 150 kV were performed in a circulation phantom. First, injections with IDR ranging from 0.1 to 2.0 g I/s were tested for each kV. In the second part, the IDR was held constant, whereas the CM volume was reduced from 50 to 10 mL. Diagnostic aortic peak enhancement for each kV was compared using the Kruskal-Wallis test. P < 0.05 was considered statistically significant. Results: The mean aortic peak enhancement for all diagnostic IDRs was 368.7 ± 11.1 HU. Diagnostic IDRs returned similar aortic peak enhancement values for all protocols (all P ≥ 0.18). For the second part of the study, a diagnostic enhancement was yielded by using a minimum of 30 mL of CM for 110 kV, 25 mL for 100 and 90 kV, and 15 mL for 80 and 70 kV. Conclusion: Our study suggests that a differentiated approach reducing the CM volume for tube voltages of less than 120 kV and increasing the IDR for higher kV settings seems to be the most effective approach.